Te hexagonal nanotubes with fast 1-dimensional Zn ion diffusion for high-performance zinc-ion battery cathodes - Kim, Mihyun; Kim, Hyosik; Lee, Si-Hwan; Yu, Seungho; Kim, Won; Bae, Jong-Seong; Ahn, Chi-Yeong; Shim, Hyungwon; Lee, Ji Eun; Yu, Seung-Ho (Elsevier BV, 2024)
The need for advanced next-generation secondary batteries have been urgently demanded for improved, sustainable, and eco-friendly energy storage systems. Aqueous rechargeable zinc ion batteries (ARZIBs) have garnered substantial attention as a substitute for lithium-ion batteries owing to their exceptional stability, environmentally friendly features, and cost-effectiveness. In this study, it is found that tellurium hexagonal nanotubes with a unique crystal growth orientation of [001] are of promising cathode materials for enhancing the performance of zinc ion batteries owing to their outstanding reaction kinetic properties. Additionally, the hollow interior of the nanotubes effectively mitigates the volume changes of tellurium during the charging and discharging processes. These research findings are expected to solidify the potential of tellurium hexagonal nanotubes as reliable cathode materials, significantly contributing to the commercialization of zinc ion battery technology in the future.